When the Victor Cannot Claim the Spoils: Institutional Incentives for Professionalizing Patronage States - Christian Schuster (Inter-American Development Bank (IDB), 2016)
Merit-based selection of bureaucrats is central to state capacity building, yet rare in developing countries. Most executives instead favor patronage -political discretion- in public employment. This paper proposes and tests an original theory to explain when executives forsake patronage for merit. The theory exploits exogenous variation in the institutional design of patronage states. In some, constitutions and budget laws monopolize patronage powers in the executive; in others, patronage benefits accrue to the legislature and public employees. When institutions fragment patronage powers and challengers control other government branches, merit becomes more incentive-compatible: it enables executives to deprive challengers of patronage while enhancing public goods provision to court electoral support. Drawing on 130 face-to-face elite interviews, a comparison of reforms in Paraguay, the Dominican Republic and the United States validates the theory. How patronage states are institutionally designed thus shapes their reform prospects: fragmented control over bad government can incentivize good government reforms.
hdl:11319/7572
Keywords: N46; D73; H11; M51; O17; 330; Institutions; Patronage; Civil service reform; State capacity; Bureaucracy